Staphylococcus aureus lipoproteins promote abscess formation in mice, shielding bacteria from immune killing - Majd Mohammad (Nature Portfolio, 2021)
Mohammad et al. show that subcutaneous injection of Staphylococcus aureus lipoproteins (Lpp) leads to the infiltration of neutrophils and monocytes/macrophages, inducing skin lesions in mice. They find that S. aureus Lpp promotes abscess formation, which protects bacteria from innate immune killing, suggesting an intriguing bacterial immune evasion mechanism.